Utilisation of Siamese Orange Waste (Citrus x aurantium L) as an Alternative Stress Reducer for First-Year Nursing Students in Pangkal Pinang - Tajudin Tajudin; Ashar Abilowo; Ana Husnayanti (Cattleya Darmaya Fortuna, 2025)
This study aims to explore the use of Siamese orange peel waste (Citrus x aurantium L) as an alternative stress reducer for first-year nursing students at the Pangkalpinang Ministry of Health Polytechnic in 2024. Siamese orange peel contains limonene compounds, which are believed to reduce stress. This study used a pre-experimental design with a pre-post test one-group design, where observations were conducted twice, before and after treatment with Siamese orange peel aromatherapy. The sample consisted of all first-year students in the Nursing Study Programme, totalling 87 individuals, using total sampling technique. The results showed that the majority of students had high stress levels before being given pomelo peel aromatherapy, while after the treatment, the majority of respondents showed normal stress levels. Statistical analysis showed a significant difference in the stress levels of students before and after being given aromatherapy, with a p-value of 0.000 (p < 0.05). Although there was an increase in heart rate after treatment, there was no significant difference in systolic blood pressure, but diastolic blood pressure decreased. This study indicates that aromatherapy with pomelo peel waste can be an effective non-pharmacological alternative in reducing stress in students.